2023
DOI: 10.3390/antiox12081536
|View full text |Cite
|
Sign up to set email alerts
|

Doped Graphene Quantum Dots as Biocompatible Radical Scavenging Agents

Adam Bhaloo,
Steven Nguyen,
Bong Han Lee
et al.

Abstract: Oxidative stress is proven to be a leading factor in a multitude of adverse conditions, from Alzheimer’s disease to cancer. Thus, developing effective radical scavenging agents to eliminate reactive oxygen species (ROS) driving many oxidative processes has become critical. In addition to conventional antioxidants, nanoscale structures and metal–organic complexes have recently shown promising potential for radical scavenging. To design an optimal nanoscale ROS scavenging agent, we have synthesized ten types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
(133 reference statements)
0
0
0
Order By: Relevance
“…Ti/GO-NPs showed 88% for 50 µg/mL, thus Ti/GO-NPs resulted in good antioxidant properties when compared to the antioxidant studies carried out with graphene doped for various metal oxides when compared with the standard ascorbic acid which showed 10-50% at 15-65 µg/mL [34]. The antioxidant activity is typically dose-dependent in our study; as the concentration of the nanoparticles increases, the antioxidant activity also increases.…”
Section: Discussionsupporting
confidence: 49%
“…Ti/GO-NPs showed 88% for 50 µg/mL, thus Ti/GO-NPs resulted in good antioxidant properties when compared to the antioxidant studies carried out with graphene doped for various metal oxides when compared with the standard ascorbic acid which showed 10-50% at 15-65 µg/mL [34]. The antioxidant activity is typically dose-dependent in our study; as the concentration of the nanoparticles increases, the antioxidant activity also increases.…”
Section: Discussionsupporting
confidence: 49%
“…Zhou et al demonstrated the ability of SeDQDs to scavenge reactive oxygen species (ROS), while SeCQDs exhibited the potential to improve memory deficits and reduce Aβ accumulation [ 26 ]. Similarly, Bhaloo et al synthesized GQDs by heteroatom doping and evaluated their radical scavenging effects, demonstrating high biocompatibility (>80% cell viability) and antioxidant abilities in various assays [ 32 ]. Notably, Al-GQDs exhibited the highest reducing power, while others showed moderate scavenging success.…”
Section: Reviewmentioning
confidence: 99%
“…18,39,40 GQDs can scavenge free radicals by either transferring hydrogen atoms from the functional groups or through electron transfer and adduct formations from the graphitic basal plane. 5,39,41 Therefore, we hypothesized that GQDs inhibit peroxidation of lipids in biological membranes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Graphene quantum dots (GQDs) are carbonaceous nanoparticles with diameters below 30 nm consisting of graphitic basal planes with oxygen-containing functional groups around their outer periphery. Depending on the starting material and synthesis method, GQDs can contain varying extents of heteroatom doping within the basal plane, as well as different oxidation states and degrees of surface charge within the peripheral functional groups. Over the past decade, GQDs have been researched extensively for biomedical applications due to their high biocompatibility, , especially when compared to other graphene-based nanomaterials such as large graphene oxides, and carbon nanotubes, , which have been associated with acute toxicity in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation